Hematological Evaluation of Three Common Teleosts in Relation to The Environmental Changes from Trang Province, Thailand - Archig Jeamah; Sinlapachai Senarat; Suparat Kongoh; Chanyut Sudtongkong; Porntep Wirachwong; Natthawut Charoenphon; Nontawat Kawjaeng; Pahol Kosiyachinda; Anan Kenthao; Piyakorn Boonyoung (Tropical Life Sciences Research, 2023)
Hematological evaluation of fish is essential to the assessment of their physiological status. This study describes the morphometric analysis and comparison of blood cell characteristics in Zanarchopterus sp., Gerres filamentosus Cuvier, 1829 and Leiognathus decorus (De Vis, 1884). The species were collected at two locations off the coast of Trang Province, Thailand. A comparative hematological evaluation was made to assess the effects of environmental conditions on the blood of the fish. Ten individuals of each species were collected from a seagrass bed at Libong Island, where human activities are increasing, and from a secluded sandy beach. Their blood samples were analysed using the blood smear technique. Erythrocytes of all the studied fishes were either elliptical or oval. The morphometric data from both locations showed that erythrocytes were of similar size, except for those of Zanarchopterus sp. Fish from both stations showed several types of leukocytes, including neutrophils and lymphocytes.The highest proportion of leukocytes was made up of lymphocytes, followed by neutrophils. However, monocytes were only observed in fish from Libong Island and the erythrocytic nuclei of fish collected from Libong Island were both reniform and lobate. Our results show the potential of hematological evaluation as an early warning signal of environmental impacts on aquatic animals. The determination of baseline parameters could provide a tool for the monitoring of environmental quality.